Acrolein inhalation acutely affects the regulation of mitochondrial metabolism in rat lung. (15th March 2022) - Tulen, C.B.M.; Snow, S.J.; Leermakers, P.A.; Kodavanti, U.P.; van Schooten, F.J.; Opperhuizen, A.; Remels, A.H.V.
Highlights: Acrolein inhalation disrupts regulation of mitochondrial metabolism. Acute acrolein inhalation is associated with a shift towards glycolytic metabolism. Acrolein inhalation decreases the abundance of indices of mitochondrial biogenesis. Acrolein inhalation does not impact the abundance of the mitophagy machinery. Abstract: Exposure of the airways to cigarette smoke (CS) is the primary risk factor for developing several lung diseases such as Chronic Obstructive Pulmonary Disease (COPD). CS consists of a complex mixture of over 6000 chemicals including the highly reactive α, β-unsaturated aldehyde acrolein. Acrolein is thought to be responsible for a large proportion of the non-cancer disease risk associated with smoking. Emerging evidence suggest a key role for CS-induced abnormalities in mitochondrial morphology and function in airway epithelial cells in COPD pathogenesis. Although in vitro studies suggest acrolein-induced mitochondrial dysfunction in airway epithelial cells, it is unknown if in vivo inhalation of acrolein affects mitochondrial content or the pathways controlling this. In this study, rats were acutely exposed to acrolein by inhalation (nose-only; 0−4 ppm), 4 h/day for 1 or 2 consecutive days (n = 6/group). Subsequently, the activity and abundance of key constituents of mitochondrial metabolic pathways as well as expression of critical proteins and genes controlling mitochondrial biogenesis and mitophagy were investigated in lung homogenates. A transient decreasing response in protein and transcript abundance of subunits of the electron transport chain complexes was observed following acrolein inhalation. Moreover, acrolein inhalation caused a decreased abundance of key regulators associated with mitochondrial biogenesis, respectively a differential response on day 1 versus day 2. Abundance of components of the mitophagy machinery was in general unaltered in response to acrolein exposure in rat lung. Collectively, this study demonstrates that acrolein inhalation acutely and dose-dependently disrupts the molecular regulation of mitochondrial metabolism in rat lung. Hence, understanding the effect of acrolein on mitochondrial function will provide a scientifically supported reasoning to shortlist aldehydes regulation in tobacco smoke.